2014
DOI: 10.4236/jtr.2014.23018
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Risk Factors of Adverse Drug Reactions Associated Multidrug Resistant Tuberculosis Treatments in Selected Treatment Centers in Addis Ababa Ethiopia

Abstract: Introduction: The key to successful elimination of tuberculosis (TB) is treatment of cases with optimum chemotherapy. Irrational anti-TB drug use over time has led to drug-resistant TB. The treatment of MDR-TB with second line drugs is long, complex and costly, and has a considerable rate of adverse effects. The level of ADR reporting is low in Ethiopia due to different factors. This Study conducted in a selected treated area in Addis Ababa, Ethiopia and helped the health care centers to understand the prevale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
12
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 5 publications
8
12
1
Order By: Relevance
“…The analysis of medical records indicates that clinically diagnosed nephrotoxicity accounts for 62 (6.7%) cases while clinically diagnosed ototoxic symptoms were detected in 42 (4.8%) of subjects, of which 16 (1.7%) patients had persistence of such symptoms. This observations are comparable to other studies in the setting which reported prevalence of 8.8% renal insufficiency and 6.0% hearing impairment [21, 38] which reported comparable findings in small cohort of patients. However, ototoxic symptom finding in our study was several times lower than a study from Iran [39] which reported 14.5% auditory toxicity and Pakistan study [40] which reported 21% ototoxicity and a UK study [35] which reported 55% of ototoxicity.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The analysis of medical records indicates that clinically diagnosed nephrotoxicity accounts for 62 (6.7%) cases while clinically diagnosed ototoxic symptoms were detected in 42 (4.8%) of subjects, of which 16 (1.7%) patients had persistence of such symptoms. This observations are comparable to other studies in the setting which reported prevalence of 8.8% renal insufficiency and 6.0% hearing impairment [21, 38] which reported comparable findings in small cohort of patients. However, ototoxic symptom finding in our study was several times lower than a study from Iran [39] which reported 14.5% auditory toxicity and Pakistan study [40] which reported 21% ototoxicity and a UK study [35] which reported 55% of ototoxicity.…”
Section: Discussionsupporting
confidence: 90%
“…In Ethiopia, specific studies on two major adverse drug reactions (ototoxicity and nephrotoxicity) associated with use of injectable second-line drugs in patients treated for MDR-TB are scarce. Previous study [21] has reported the prevalence and risk factors of all adverse drug reactions associated with MDR-TB treatment in two treatment centers in Addis Ababa. This study was a cross-sectional study which used small number ( n = 72) patients and children were excluded despite their high risk for toxicity [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Censored was defined as a DR-TB patient who didn’t develop any major adverse drug event at the end of the study, transferred out, cured, completed, failed or lost to follow up before developing any major adverse drug event. Major adverse drug events are serious adverse events that are often complicated to monitor and can be life threatening to warrant extra attention in monitoring for early detection and prompt management pertaining to the following medical conditions [4, 5, 22].…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have reported the risk factors associated with adverse drug reactions due to tuberculosis drugs (10,(23)(24)(25). Chung-Delgado, Revilla-Montag (10) conducted a study in Lima-Peru and found that old age (over 40 years), anemia, medication for multidrug resistant tuberculosis, overweight/obesity status, and smoking history are independent risk factors associated with ADRs due to antituberculosis treatment.…”
Section: Introductionmentioning
confidence: 99%